“EVERYTHING ABOUT US IS FEMINIST”: The Significance of Ideology in Organizational Change - Thomas, Jan E. (Gender & Society, 1999)
This study explores the role feminist ideology played in long-term structural changes in feminist organizations. The vehicle for this exploration was a comparative case study of 14 feminist women's health centers that were started in the 1970s and were still in existence in the early 1990s. Drawing on interviews and site visits, the author describes the early collectivist structures, highlights some of the crises these organizations faced, and describes three structural ideal types that emerged in the 1990s. The analysis suggests three ideological issues that directed structural change: the importance of maintaining a system for the equitable distribution of power, the importance of growth versus autonomy, and the importance of feminism as an organizational outcome or internal process.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem7000; justice sociale; militance; organisations féministes; pratiques féministes; périodes historiques; recherche participative; régions géographiques; sciences humaines; structures organisationnelles; thématiques; travail social; états-unis; étude de cas

Privilege: Expanding on Marilyn Frye's "Oppression" - Bailey, A. (JOURNAL OF SOCIAL PHILOSOPHY -AUGUSTA-, 1998)
This essay serves as both a response and embellishment of Marilyn Frye's now classic essay " Oppression." It is meant to pick up where this essay left off and to make connections between oppression, as Frye defines it, and the privileges that result from institutional structures. This essay tries to clarify one meaning of privilege that is lost in philosophical discussions of injustice. I develop a distinction between unearned privileges and earned advantages. Clarifying the meaning of privilege as unearned structural advantage makes visible the role white privilege plays in maintaining complex systems of domination such as racism, sexism, heterosexism and classism. Using a critical reading of both Frye and Young's accounts of oppression as a springboard, I develop a definition of privilege as a particular class of unearned advantages. -/- I distinguish my account of privilege from standard legal and philosophical definitions of privilege. The general distinction I make between privileges and advantages rests on three interrelated claims: that benefits granted by privilege are always unearned and conferred systemically to members of dominant social groups; that privileges granted to members of dominant groups solely on the basis of their membership in these groups is never justifiable; and, that privileges have an unconditional value that can be explained not only in terms of immunities, but also in terms of additional benefits
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; fem9000; justice sociale; phi4336; philosophie; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Feminist contentions: A philosophical exchange - Benhabib, Seyla; Butler, Judith; Cornell, Drucilla; Fraser, Nancy (Routledge, 1995)
Ce volume présente un débat entre quatre des plus grandes théoriciennes féministes des États-Unis. Seyla Benhabib, Judith Butler, Drucilla Cornell et Nancy Fraser discutent de certaines des questions clés auxquelles la théorie féministe est confrontée. Chacune articule sa propre position dans un essai initial, puis répond aux autres dans un essai de suivi, rendant possible une conversation entre ces penseuses féministes influentes. Commencé comme un symposium sur la question du féminisme et du postmodernisme, le volume s'est transformé en une discussion sur des questions plus larges telles que l'utilité du postmodernisme en tant que concept théorique; le rôle de la philosophie dans la critique sociale ; comment le récit historique est le mieux conceptualisé ; le statut du sujet du féminisme ; et les effets politiques des différentes formulations de toutes ces questions.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; postmodernisme; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis

Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberlé William (Stanford Law Review, 1991)
Contemporary feminist and antiracist discourses have failed to consider the intersections of racism and patriarchy. To overcome this difficulty, an original approach is suggested here: that of intersectionality. In the first part, the paper discusses structural intersectionality, the ways in which the location of women of color at the intersection of race and gender makes their real experience of domestic violence, rape, and remedial reform qualitatively different from that of white women. The focus is shifted in the second part to political intersectionality, with the analysis of how both feminist and antiracist politics have functioned in tandem to marginalize the issue of violence against women of color. Finally, the implications of the intersectional approach are addressed within the broader scope of contemporary identity politics.
Keywords: 1900-1999; OFDIG; afro-féminisme; amériques; antiracisme; approches et analyses; cours; cycles supérieurs; fem9000; femmes* afro-américaines; féminismes noirs; incontournable; intersectionnalité; militance; patriarcat; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; violences raciales; états-unis

Les théories scientifiques ont-elles un sexe? : actes du colloque - Decerf, Anne (Éditions d'Acadie, 1991)
Keywords: amériques; approches et analyses; canada; cours; cycles supérieurs; discipline; fem9000; inégalités; régions géographiques; sciences; sexisme; systèmes d'oppressions